The natural history of non-arteritic anterior ischaemic optic neuropathy. - Sawle, G V (1990)
Seventy one patients with non-arteritic anterior ischaemic optic neuropathy were studied retrospectively. Sixty three (89%) were followed to the end of the study or death, mean follow up time was 5.3 years. Whilst twenty (28%) had diabetes or hypertension, in thirty nine (55%) no predisposing condition was identified. In those who had monocular disease at presentation (68), subsequent involvement of the second eye occurred in seventeen (25%), seven within the first year. Nineteen patients died within the study period. Of these, nine died from myocardial infarction and four from cerebrovascular disease. This is a significant increase above figures calculated from the Office of Population Census and Surveys (p less than 0.001 for all causes, p less than 0.002 for myocardial infarction and cerebrovascular disease). Such an increase in mortality has not been previously reported, and implies that this condition carries a more sinister systemic prognosis than is frequently supposed.